Answer:
Part 1 = [tex]\frac{4a^{2} -b^{2} }{2a-b}[/tex]
Part 2 = [tex]\frac{6a^{2} +3ab }{3a}[/tex]
Step-by-step explanation:
Let the fraction be denoted by numerator and denominator then given denominator for the first expression contains 2a-b.
let us assume that the numerator contains x
now given that 2a+b is the value of the expression which means
[tex]2a+b=\frac{x}{2a-b}[/tex]
[tex]x=4a^{2} -b^{2}[/tex]
Therefore the fraction for the first option is [tex]\frac{4a^{2} -b^{2} }{2a-b}[/tex]
Given the denominator for the second expression is 3a.
Let us assume that the numerator contains x
Now given that 2a+b is the value of the expression which means
[tex]2a+b=\frac{x}{3a}[/tex]
[tex]x=6a^{2} +3ab[/tex]
Therefore the fraction for the second option is [tex]\frac{6a^{2} +3ab }{3a}[/tex]